Penyuluhan Energi Tepat Guna dengan Penggunaan Lampu Hemat Energi di RW 004, Kelurahan Kamal, Kecamatan Kalideres, Jakarta Barat - Az, Nazori; Fath, Nifty; Sirait, Rummi (Indonesian Journal of Emerging Trends in Community Empowerment, 2023)
Socialization on appropriate energy using energy-saving lamps in RW 004, Kamal Village, Kalideres District, West Jakarta aims to provide an understanding of how to use energy-saving lamps and save energy to residents in RW 004, Kamal Village, Kalideres District, West Jakarta. This extension activity was carried out using an interactive presentation method. This activity consists of three sessions, namely a presentation on energy saving measures, then a presentation on energy saving lamps and ending with a discussion. This activity received high enthusiasm from residents. Therefore, this education really needs to be developed and carried out in a sustainable manner so that people can continue to broaden their knowledge about energy.